What Do We Mean by “Reform?”: On the Seductiveness of Reform in Teaching and Teacher Education and It's Mischievous Influences - Bullough, Robert V. (Frontiers in Education, 2021)
Drawing on literary critic Kenneth Burke's concept of "terministic screens," the author explores some of the history and a few of the troubling implications for the work of teachers and teacher educators that flow from the idea of reform. Concluding that "reform is a bad idea", the author argues for an alternative conception of educational improvement, one that is more life-affirming and hopeful. Seeking to weaken the conceptual and ethical hold of reform on policy-makers and educators, the author argues with John Goodlad that educational improvement first and foremost must be understood as a learning problem, an issue of educational renewal.